Very first questions and answers Why should i get dressed? - Daynes, Katie; Harrison, Suzie; Miguens, Marta Alvarez (London Usborne house, 2021)
Flaps, facts and an exciting range of outfits will inspire kids to get dressed for the day. From sports kit and superhero costumes to coats and wellies, this delightful book makes getting dressed fun
Scientific notions
Keywords: Science